2022
DOI: 10.1055/a-1858-1810
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Microbiota Monitoring in Elite Soccer Players Along the 2019–2020 Competitive Season

Abstract: Physical exercise affects the human gut microbiota that, in turn, influences athletes’ performance. The current understanding of how the microbiota of professional athletes changes along with different phases of training is sparse. We aim to characterize the fecal microbiota in elite soccer players along with different phases of a competitive season using 16S rRNA gene sequencing. Fecal samples were collected after the summer off-season period, the pre-season retreat, the first half of the competitive season, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Further studies with larger sample sizes are needed to confirm these findings and to better understand the changes in gut microbiota throughout an athletic season. Among the limited studies in this area, one report examined the changes in the gut microbiota of professional soccer players during the season [20] and found that the most variation occurred at the start of the season. Taking this into consideration, the beginning of an athletic season could be interpreted as the time when the modified gut microbiota associated with the off-season is returning to the state associated with the athletic season.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies with larger sample sizes are needed to confirm these findings and to better understand the changes in gut microbiota throughout an athletic season. Among the limited studies in this area, one report examined the changes in the gut microbiota of professional soccer players during the season [20] and found that the most variation occurred at the start of the season. Taking this into consideration, the beginning of an athletic season could be interpreted as the time when the modified gut microbiota associated with the off-season is returning to the state associated with the athletic season.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests potential changes in the gut microbiota of athletes throughout a season. Among the limited studies in this area, one report examined the changes in gut microbiota of professional soccer players during the season [19] and found that the most variation occurred at the start of the season. Taking this into consideration, the beginning of an athletic season could be interpreted as the time when the modified gut microbiota associated with the off-season is returning to the state associated with the athletic season.…”
Section: Discussionmentioning
confidence: 99%
“…All specimens were stored at -20°C until processing. Total microbial DNA for each fecal sample was extracted through a method combining bead-beating and column purification, as described previously [15].…”
Section: Methodsmentioning
confidence: 99%